The Influence of Price and Promotion on Purchasing Decisions for Honey Products - Nufus, Sofia; Dipayanti, Kris (Indonesian Development of Economics and Administration Journal, 2025)
The purpose of this study was to determine the effect of price and promotion on consumer purchasing decisions for calliandra honey products at the Nima Bali Store in South Jakarta. This type of research uses associative research, with a quantitative approach. The population in this study amounted to 2,751 consumers and the sample in this study amounted to 96 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Partially indicates there is a significant influence between price on consumer purchasing decisions, significant influence between promotion on consumer purchasing decisions. And simultaneously results showed by F hypothesis test obtained a significance influence price (X1) and promotion (X2) on consumer purchasing decisions (Y)